Taking Public Opinion Seriously: A General Equilibrium Model of Low-Wage Competition, Offshoring, and Unemployment - Lutz G. Arnold; Stefanie Trepl (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2011)
This paper analyzes a North-South trade model with costly offshoring and equilibrium unemployment due to union wage setting. Reductions in the amount of resources required in the offshoring process usually decrease employment, though the opposite can happen at a low initial level of offshoring activity. If additional offshoring leads to a fall in the scale of Northern firms, the increase in Southern workers' utility comes at the expense of a reduction in each Northern agent's welfare. The model can be used to make a case for a 'pragmatic union leader': unions have an incentive to take measures that reduce their bargaining power. With firm heterogeneity, there is scope for multiple equilibria.
Keywords: F12; J64; 330; offshoring; unemployment; North-South trade; Auslandsverlagerung; Arbeitslosigkeit; Nord-Süd-Beziehungen; Niedriglohn; Internationaler Wettbewerb; Allgemeines Gleichgewicht; Gewerkschaftspolitik; Lohnverhandlungen; Theorie